Empiricism and Common Sense: the Management of Public Health in the Kingdom of Sicily (1575-1860) - Craxì, Lucia (Medicina Historica, 2020)
The research outlines the evolution of the public health management system in the Kingdom of Sicily between the second half of the 16th century and the first half of the 19th century, emphasizing the specific features of the Sicilian case and highlighting the possible causes. It frames the evolution of public health institutions in Sicily both in the process of centralization and organization of the administrative apparatus of modern State, and in the development of medical theories concerning contagion. Through the analysis of the legislation and of the documentation produced by the competent bodies, it has been proved that there is no break in continuity in the activity of the various institutions that manage public health along the time span investigated. Special attention is devoted to the role of doctors within these institutions and to the relationship with medical science. The analysis shows that the competent bodies based their choices on an empirical approach, making prudential choices that took into account both the miasmatic theory and the contagionist theory.